Aspectos clínico-epidemiológicos de pacientes com o vírus da imunodeficiência humana e marcadores sorológicos para o vírus da hepatite B atendidos na Casa Dia, Belém, Pará, 2007 - SANTOS, Bruna Cristina Lobo (2022)
The human imunodeficincy virus (HIV) and hepatitis B virus uses the same route of transmission, being the prevalence of hepatitis B virus in patients infected with HIV bigger than the one found in the general population. This research aims to know the aspects physician-epidemiologistics of HIV patients that presents sorologics markers for hepatitis B virus, taken care in Casa Dia, in Belém. For the attainment of the data, a retrospective study was become fullfilled and transversal, between December 2006 and March 2007, when it was revised handbooks and applied a questionnaire standard. Of the studied patients, 85.4% (n=854) had not made sorology for Hepatitis B and 73.20% had received vaccine anti-HBV. It was observed that 88% of participants of the research inhabit in the state of Pará, being 91% of these (n=30) of masculine sex and 73% of the patients (n=20) are single and 76% (n=25) have ages between 30 and 49 years. Analyzing the risk factors, it could be observed that it had equal amount of heterosexuals and men who make sex with men and 91% of the patients (n=30) did not use condoms during the sexual relations. Five patients, 15%, presented linfocits T CD4+ lesser than 200 célls/mm ³. In relation to the sorologics markers of Hepatitis B, 25 patients presented anti-HBc IgG positives and 16, anti-HBs. The HBsAg appeared in eight patients. The clinical manifestations associates to HIV were present in 93,94% of the studied patients, being that, in general, more one symptom in each patient. The most frequents had been asthenia, observed in 63,63% of these, followed of cough and dispeptics symptoms, in 57,57% of the cases. Although the similarity in the ways of transmission of HBV and HIV justify the meeting of a bigger risk of infection for the HBV, the results found in this work shows that the incidence of the sorologics markers for hepatitis B in HIV positive patients of Casa Dia in Belém is not so significant (3.3%).